2005
DOI: 10.1063/1.1846137
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of alumina nanotubes and nanowires from highly ordered porous anodic alumina template

Abstract: Alumina nanotube (ANT) and nanowire (ANW) arrays were produced from highly ordered porous anodic alumina (PAA) by etching in phosphoric acid and subsequent thermal treatment. The domain structures that have small sizes provide more boundaries and break the hexagonal symmetry of the PAA template, thereby inducing star-like splitting modes. Using very thin PAA films, ANTs and their arrays are fabricated, whereas ANWs and their arrays are produced when using thick films. This is due to the thin wall between nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…The electric field is not present in the case [16] of etching PAAO using a phosphoric acid solution, and a nonuniform electric field develops in the peripheral zones of the sample in this paper. This indicates that pores and nanowires can form when corrosive solutions make contact with aluminum or alumina oxide.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The electric field is not present in the case [16] of etching PAAO using a phosphoric acid solution, and a nonuniform electric field develops in the peripheral zones of the sample in this paper. This indicates that pores and nanowires can form when corrosive solutions make contact with aluminum or alumina oxide.…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies confirm the formation of alumina oxide nanowires via the immersion of PAAO into various kinds of acid or alkaline solutions [14,16]. Nanowires, which grew as a consequence of the treatment using 10 wt% sulfuric acid solution, were concentrated on top of the undissolved porous alumina oxide layers.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this sense, several groups of authors reported different alumina nanostructures that were fabricated via a simple etching method in NaOH [4][5][6][7] or in a chromic and phosphoric acid solution [1,7]. Alternatively, Mei et al [8] produced alumina nanotube and nanowire arrays by etching the AAO in 5%w phosphoric acid solution and subsequent thermal treatment. The diameter of the nanowires is about 30-40 nm, which corresponds to the thickness of the wall between the nanopores.…”
Section: Introductionmentioning
confidence: 98%
“…These templates could be nanoporous membranes or nanofibers. In this context, aerogels could be used as facile highly porous templates for nanostructured alumina [9, 10, 11, 12].…”
Section: Introductionmentioning
confidence: 99%